2023
DOI: 10.1111/jdv.19498
|View full text |Cite
|
Sign up to set email alerts
|

A novel SERPINA12 variant and first European patients with diffuse palmoplantar keratoderma

E. Brandt,
L. Harjama,
O. Elomaa
et al.

Abstract: BackgroundHereditary palmoplantar keratodermas (hPPKs) comprise a heterogeneous group of skin disorders characterized by persistent palmoplantar hyperkeratosis. Loss‐of‐function variants in a serine peptidase inhibitor, SERPINA12, have recently been implicated in autosomal recessive diffuse hPPK. The disorder appears to share similarities with another hPPK associated with protease overactivity, namely Nagashima‐type PPK (NPPK) caused by biallelic variants in SERPINB7.ObjectivesThe aim of this study was to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…SERPINB7-associated PPKs are clinically indistinguishable, suggesting the necessity of genetic evaluation. 7 The study by Brandt et al expands the spectrum of pathogenic SERPINA12 variants, and further underscores the crucial roles of serine protease inhibitors in maintaining normal differentiation of the palmoplantar epidermis in humans.…”
Section: Commentarymentioning
confidence: 98%
See 4 more Smart Citations
“…SERPINB7-associated PPKs are clinically indistinguishable, suggesting the necessity of genetic evaluation. 7 The study by Brandt et al expands the spectrum of pathogenic SERPINA12 variants, and further underscores the crucial roles of serine protease inhibitors in maintaining normal differentiation of the palmoplantar epidermis in humans.…”
Section: Commentarymentioning
confidence: 98%
“…Of these, two patients were homozygous for a recurrent nonsense variant c.631C > T (p.Arg211*), while one was compound heterozygous for the variant c.631C > T and a novel missense variant c.1100G > A (p.Gly367Glu). 7 Therefore, the authors have revealed, for the first time, that there are patients with the SERPINA12-associated PPK in European populations. Furthermore, they clearly showed that the c.631C > T in the SERPINA12 was a founder variant in the Finnish population.…”
mentioning
confidence: 97%
See 3 more Smart Citations